INTERVENTION TO REDUCE STRESS LEVELS IN PEOPLE WITH HIV/AIDS: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.78 - Nancy Indriyani Dida (Alta Dharma Publisher, 2019)
Abstract People living with HIV/AIDS experience a variety of complex problems, not only physical problems related to the condition of HIV disease, but also psychosocial problems related to HIV disclosure, stigma, social isolation and discrimination that can cause anxiety and cause high stress levels.The conditions will gave the negative impact on both physical and mental health. The negative impact of stress can lead to depression, giving rise to an attitude of non-compliance with treatment, increased risk behavior for HIV transmission and faster disease progression, which in turn will worsen the quality of life for people living with HIV/AIDS. Several studies have been conducted to found appropriate interventions to reduce stress levels in people with HIV/AIDS. This article is a literature review of several interventions to reduce stress levels in people with HIV/AIDS, included Jacobson's Progressive Muscle Relaxation (JPMR), Mindfulness-Based Stress Reduction (MBSR) and Reiki therapy. Literature search was carried out from databases such as Pubmed, EBSCOhost, Scopus, Proquest, Sciene Direct, with limited years of article publication in the last 10 years (2008-2018). Based on the review, it was found that Jacobson's Progressive Muscle Relaxation (JPMR) intervention; Mindfulness-Based Stress Reduction, Reiki Therapy shows very significant results in decreasing stress levels in people with HIV conducted in three studies with different interventions. Keyword: Stress, HIV/AIDS, intervention